ปัจจัยส่วนประสมทางการตลาดที่ส่งผลต่อการตัดสินใจเลือกใช้บริการสระว่ายน้ำในประเทศไทย - มะหะหมัด ทศพร; ภูมิจิตอมร อารยะ; วิสิฐนิธิกิจา ชิณโสณ์ (Thai Interdisciplinary and Sustainability Review, 2021)
This research aimed to study 1) to study the marketing mix factors affecting swimming pool service in Thailand 2) to study the decision to use swimming pool service in Thailand 3) to compare the decision to use swimming pool Swimming in Thailand 4) To study the relationship between marketing mix factors and the decision to use swimming pool services in Thailand. The data were collected from 400 questionnaires. The statistics used for data analysis were The descriptive statistics were frequent, percentage, mean, and inferential statistics used in hypothesis testing, namely Independent-Sample T-Test, ANOVA analysis using an F - test, (One-way ANOVA), Pearson Product Moment Correlation and Multiple Regression Analysis. The results showed that most of the respondents were female, aged 21-30 years and 41-50 years. To exercise a career contractor / company employee Bachelor’s degree and the average monthly income is more than 50,000 baht. Marketing mix factors affecting the decision to use swimming pool services in Thailand as a whole are of great importance. The overall decision-making process with a medium level of importance. Hypothesis test results Different gender, personal factors have different pool service decision-making processes. Marketing mix factors are related to the decision of choosing a swimming pool service in Thailand. Distribution channels and marketing promotion in general, there is a relationship to the decision-making process of using swimming pool services in Thailand. Medium correlation level, same direction and price side, low correlation level. Factor of marketing mix, price, distribution channel marketing promotion and personal influences on swimming pool service decisions in Thailand. With statistical significance at the .05 level. Recommendations From the results of the study, the pool business operators in Thailand should pay more attention to maintaining the water quality standard. Not harmful to the user. Clear price tags for all types of services Opening a property in a location with convenient transportation Organize promotional activities in ways that create attractive service decisions. Provide a knowledgeable trainer who can teach swimming Maintain the safety of the service users at all times the service is open. The environment of the swimming pool is clean, beautiful and tidy